Integrasi Hafalan Mufrodat Dalam Pembelajaran Bahasa Arab: Upaya Meningkatkan Literasi Teks Arab Siswa Ma Al-Ittihad Malang - Mulloh, Tamim (AL-FIKRA, 2025)
This study aims to examine the influence of integrating vocabulary memorization (mufrodat) through the mahfudzat method in Arabic language learning on improving students' Arabic text literacy at MA Al-Ittihad Malang. This research employs a descriptive qualitative approach with data collection techniques including observation, in-depth interviews, and documentation. The results show that the mahfudzat method has a positive impact on students' vocabulary retention, interest in learning Arabic, and understanding of text structure and meaning. Students find it easier to memorize vocabulary when it is presented in meaningful and rhythmic sentences. In addition, teachers implement various learning strategies to accommodate students' differing abilities. Challenges such as limited time and differences in memorization capacity are addressed through gradual learning and group activities. Thus, the integration of the mahfudzat method is proven to be effective in significantly improving students’ Arabic text literacy.